Theory and Observation of Active B-type Stars - Cidale, Lydia Sonia; Kraus, Michaela; Arias, María Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Active B-type stars are defined by their characteristic emission formed in a dense environment. Among them are the classical Be stars, which are surrounded by ionized gaseous disks, and B[e] stars, whose disks are so dense that even molecules and dust can form within them. The variability of active B-type stars seen on various time and spatial scales is often connected to the formation and dissipation of these disks. Although the possible roles of radiation, rotation, pulsation, and binarity in pulling material off the stars have been explored in detail in the past few decades, the relevant physical processes involved in the formation of sustainable disks and their dynamical evolution are still unclear and a matter of debate.This Special Issue intends to provide a comprehensive update on the state of knowledge in the field of active B-type stars. It combines reviews and selected contributions on recent groundbreaking advancements in the comprehension of these peculiar objects from both a theoretical and an observational perspective. These new insights form the basis for exploring complex physical phenomena to verify the different scenarios proposed for the evolution and variability of stars and their circumstellar environment of the diverse classes of active B-type stars.